Dissolved organic carbon in water f luxes of Eucalyptus grandis plantations in northeastern Entre Ríos Province, Argentina = Carbono orgánico disuelto en flujos hídricos de plantaciones de Eucalyptus grandis del noreste, provincia de Entre Ríos, Argentina - Teson, Natalia; Conzonno, Víctor H.; Arturi, Marcelo Fabian; Frangi, Jorge L. (Facultad de Ciencias Forestales y Recursos Naturales, Universidad Austral de Chile, 2019)
Water fluxes in tree plantations and other ecosystems carry dissolved organic carbon (DOC) provided by atmospheric inputs, autotrophic and heterotrophic metabolisms and from the lysis of dead material. These compounds may be colorless or provide a yellow-to-brown color to water and may also absorb visible light due to the presence of chromophores in the chemical structure. Concentration and composition of DOC and DOC annual flux in water pathways of a Eucalyptus grandis plantation were studied in Entre Ríos, Argentina. Samples of bulk precipitation, throughfall, stemflow, litter lixiviation, surface runoff and water table were analyzed for DOC concentration and color (optical density). Regression analyses for DOC concentration vs water fluxes intensity and for DOC concentration vs color were done. A DOC circulation model was calculated using available information on water budgets fluxes. Results showed that molecular features, values and range of DOC concentrations varied among fluxes, which may be explained by factors and processes influencing water gains and losses and by composition and availability of organic matter that may be dissolved in water in contact with biomass, necromass, soil and subsoil. Regression parameters from DOC concentration vs optical density were useful for DOC chemical composition analyses and interpretation of DOC changes. Annual circulation of DOC (in kg ha-1 year-1) showed that atmospheric contribution is low (ca. 30), aboveground biomass lixiviation is about 3-4 times the atmospheric input (126.7 to 101.4), and inputs to mineral soil (374.4 to 348.0) came mainly (74 to 78 %) from litter lixiviation